Antecedents and outcomes of interpersonal influences and the role of acculturation: The case of young British-Muslims - Jamal A.; Shukor S.A. (2024)
Prior research considers antecedents and outcomes of interpersonal influence without consideration of acculturation. Data collected from 222 young British-Muslims using focus groups, in-depth interviews and questionnaires identifies significant antecedents and outcomes concluding that self-congruity, clothing conformity, need for uniqueness and modesty are major contributors to susceptibility to interpersonal influence. Acculturation moderates the effects of self congruity and susceptibility to interpersonal influence. The paper discusses implications for clothing retailers suggesting that self-congruity, conformity and modesty require closer attention to develop effective promotion and product strategies. The study is first of its kind within the UK ethnic minorities market. 2013 Elsevier Inc.